The identity of Ligularia chekiangensis (Asteraceae, Senecioneae) - Wang, Long; Ren, Chen; Yang, Qin-Er (Phytotaxa, 2017)
Ligularia chekiangensis (Asteraceae, Senecioneae) is considered to be conspecific with L. fischeri and is synonymized.